The Application of Statistical Design of Experiments to Study the In-Plane Shear Behaviour of Hybrid Composite Sandwich Panel - Jauhar Fajrin (Civil Engineering Dimension, 2016)
This paper presents a statistical aspect of experimental study on the in-plane shear behaviour of hybrid composite sandwich panel with intermediate layer. The study was aimed at providing information of how significant the contribution of intermediate layer to the in-plane shear behaviour of new developed sandwich panel. The investigation was designed as a single factor experimental design and the results were throughly analysed with statistics software; Minitab 15. The panels were tested by applying a tensile force along the diagonal of the test frame simulating pure shear using a 100 kN MTS servo-hydraulic UTM. The result shows that the incorporation of intermediate layer has sinificantly enhanced the in-plane shear behaviour of hybrid composite sandwich panel. The statistical analysis shows that the value of F0 is much higher than the value of Ftable, which has a meaning that the improvement provided by the incorporation of intermediate layer is statistically significant.